2009
DOI: 10.3109/14992020903079332
|View full text |Cite
|
Sign up to set email alerts
|

Benefit from spatial separation of multiple talkers in bilateral hearing-aid users: Effects of hearing loss, age, and cognition

Abstract: To study the spatial hearing abilities of bilateral hearing-aid users in multi-talker situations, 20 subjects received fittings configured to preserve acoustic cues salient for spatial hearing. Following acclimatization, speech reception thresholds (SRTs) were measured for three competing talkers that were either co-located or spatially separated along the front-back or left-right dimension. In addition, the subjects' working memory and attentional abilities were measured. Left-right SRTs varied over more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 52 publications
9
66
1
Order By: Relevance
“…There were, nonetheless, nine individuals who demonstrated masking release of 2 dB or greater, suggesting that they had access to spatial cues when wearing bilateral hearing aids and were able to use the cues for speech unmasking. Consistent with findings from Marrone et al (2008a), Neher et al (2009), andAhlstrom et al (2009) on adult users of bilateral hearing aids and earlier data on children (Ching et al, 2005), the present results suggest that spatial advantages are possible with current hearing-aid technology and fitting in conditions where no adaptive features were engaged. Larger spatial advantage would be expected if directional microphones were used, but such use was not routine clinical practice for children at the time the data were collected.…”
Section: B Srm: Effect Of Age and Hearing Thresholdssupporting
confidence: 81%
“…There were, nonetheless, nine individuals who demonstrated masking release of 2 dB or greater, suggesting that they had access to spatial cues when wearing bilateral hearing aids and were able to use the cues for speech unmasking. Consistent with findings from Marrone et al (2008a), Neher et al (2009), andAhlstrom et al (2009) on adult users of bilateral hearing aids and earlier data on children (Ching et al, 2005), the present results suggest that spatial advantages are possible with current hearing-aid technology and fitting in conditions where no adaptive features were engaged. Larger spatial advantage would be expected if directional microphones were used, but such use was not routine clinical practice for children at the time the data were collected.…”
Section: B Srm: Effect Of Age and Hearing Thresholdssupporting
confidence: 81%
“…Listeners with hearing impairment (HI) often demonstrate reduced SRM compared to listeners with normal hearing (NH) in multitalker listening situations (e.g., Marrone et al, 2008;Neher et al, 2009;Glyde et al, 2013b), leading to the common notion that spatial processing is disrupted by hearing loss. However, attempts to provide convergent evidence from other kinds of spatial tasks have produced very mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…This confirms the findings of multiple previous studies (Lunner, 2003;Foo et al, 2007;Lunner and Sundewall-Thorén, 2007;Neher et al, 2009;Souza et al, 2010;Rudner et al, 2011;Ng et al, 2013). Although hearing loss (PTA) and WM capacity (RS score) were statistically unrelated, the two factors explained 22.6% of the variance in the speech-recognition performance.…”
Section: Behavioural and Neural Findings Support The Elumodelsupporting
confidence: 81%
“…Two (Neher et al, 2011;Zekveld et al, 2014) out of three studies (Neher et al, 2009) investigating the relationship between the RS score and speech understanding of spatially separated sounds, similarly observed no relation between the two. In one of the studies, a significant effect of attention was found on the speech recognition (Neher et al, 2011).…”
Section: Behavioural and Neural Findings Support The Elumodelmentioning
confidence: 89%